A Strategy for IMF Engagement on Social Spending : Case Studies. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2019)
This paper uses case studies to explore the nature and extent of past IMF engagement on social spending issues and to draw lessons for future engagement.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet